Gothorum romanorumque consensus. Jedność Gotów i Rzymian w działalności politycznej Amalasunty - Skibiński, Tomasz (Vox Patrum, 2016)
The article presents the reign of Amalasuntha – Theodoric the Great’s daughter – from the point of view of her endeavours for the unity and integration of the Goths and Romans in the Ostrogothic Kingdom. Analysis of the most important sources on the subject reveals her efforts in the following areas: concern for social justice and attempts to remedy the difficult situation in the country which had arisen in the last years of Theodoric; emphasis on the unity of the Goths and Romans in letters sent to various persons on behalf of Athalaric; concern for the religious unity of Roman Catholics and Arian Goths; attempts to provide the best education for Athalaric according to the style adopted in Roman society. The premature death of Athalaric, and shortly after, of Amalasuntha, did not allow her to realize her plans. Following her death, the Byzantine army began the reconquest of Italy. This also, meant the fall of her political programme, and the Ostrogoth Kingdom soon disappeared from the map.